Determinants of Social Security Financing in Algeria: A Marketing Approach using a Logit Model - Guellil, Nassima; Benhabib, Abderrezzak (Journal of Social Economics Research, 2022)
Social security is an important tool aimed at ensuring the social protection of individuals against social risks. However, almost all countries face problems linked to social security financing because their resources are insufficient to cover their expenses. This funding problem is related to the efficiency in the collection of contributions, as the contribution of the working population to the financing of social security can ensure its sustainability. Although social security is mandatory, the absence of funding participation by many people in Algeria contributes to a deepening of the funding crisis. This study aims, first, to examine the extent to which the employed population can finance Algerian social security and, second, to uncover the factors that cause the private sector to refrain from participating in the financing of social security in Tlemcen. Our methodology draws on a marketing approach using the logit model, which reveals that three types of factors have the greatest influence on the participation of individuals in the financing of social security: socio-economic factors, individual characteristics, and the regulation system adopted by the Algerian Social Security Institution.